2006
DOI: 10.1016/j.jacc.2005.11.084
|View full text |Cite
|
Sign up to set email alerts
|

Renal Impairment and Outcomes in Heart Failure

Abstract: Renal impairment is common among HF patients and confers excess mortality. Renal function should be considered in risk stratification and evaluation of therapeutic strategies for HF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
492
3
59

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 786 publications
(584 citation statements)
references
References 40 publications
30
492
3
59
Order By: Relevance
“…For the group as a whole, the mean duration of hospitalisation was 11 ± 9 days (median, 7 days; IQR, [6][7][8][9][10][11][12][13][14][15]. Patients who developed WRF-Abs-% had a longer mean and median duration of hospital stay: 15 ± 14 days versus 8 ± 7 days (median, IQR: 12, 8-22 days versus 8, 5-14, days; p b 0.001).…”
Section: Clinical and Prognostic Significance Of Wrfmentioning
confidence: 99%
See 1 more Smart Citation
“…For the group as a whole, the mean duration of hospitalisation was 11 ± 9 days (median, 7 days; IQR, [6][7][8][9][10][11][12][13][14][15]. Patients who developed WRF-Abs-% had a longer mean and median duration of hospital stay: 15 ± 14 days versus 8 ± 7 days (median, IQR: 12, 8-22 days versus 8, 5-14, days; p b 0.001).…”
Section: Clinical and Prognostic Significance Of Wrfmentioning
confidence: 99%
“…Its prevalence increases in patients with more severe HF. More than half of the patients hospitalised for HF have some degree of impairment of renal function, and moderate to severe impairment has been reported in 30-35% of cases [7,[9][10][11][12][13]. Hospitalisation for acute HF is associated with further worsening of renal function (WRF) in 30-50% of patients, depending on the specific definition utilized, and this is associated with prolonged length of hospital stay, increased healthcare costs, increased in-hospital mortality, and higher rates of rehospitalisation and death post-discharge [9][10][11][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…At the decompensated phase of HF, the renal function worsening is a frequent occurrence 13 , possibly due to the presence of low cardiac output, use of medications and presence of comorbidities 14,15 . Svensson et al 4 identified the renal function, diabetes mellitus and the functional class of heart failure (NYHA) as independent risk factors for the development of hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac diseases are associated with decreased kidney functions and progression in kidney diseases, whereas chronic kidney disease is an independent risk factor for cardiovascular events (6,7). Glomerular filtration rate (GFR) is <60 mL/min in 30-60% of patients with HF (8)(9)(10)(11). Renal dysfunction has a greater impact on mortality than impaired cardiac function [EF and New York Heart Association (NYHA) class] in advanced HF patients (10,12).…”
Section: Introductionmentioning
confidence: 99%